2008
DOI: 10.1016/j.apergo.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A gender approach to work ability and its relationship to professional and domestic work hours among nursing personnel

Abstract: The association between working hours and work ability was examined in a cross sectional study of male (N=156) and female (N=1092) nurses in three public hospitals. Working hours were considered in terms of their professional and domestic hours per week and their combined impact; total work load. Logistic regression analysis showed a significant association between total work load and inadequate work ability index (WAI) for females only. Females reported a higher proportion of inadequate WAI, fewer professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
49
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 28 publications
10
49
0
8
Order By: Relevance
“…Akin to the results shown by another study with nursing teams (8) , it was also observed that men worked more in relation to remunerated work, when compared to women. However, the total work hours of men is less, due to reduced responsibilities in domestic work as split between them.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Akin to the results shown by another study with nursing teams (8) , it was also observed that men worked more in relation to remunerated work, when compared to women. However, the total work hours of men is less, due to reduced responsibilities in domestic work as split between them.…”
Section: Discussionmentioning
confidence: 51%
“…Together with these factors, the prevalence of females in these professions (1,3,8) means a need to also weigh in the domestic workload and also its interaction with professional employment when assessing the impact that the working hours have on health, as shown in other studies (3,5,8) . However, when considering the work within the context of the nursing profession, it is important to stress that the influence of the long working hours affects not only the health of the nursing professionals but also the standard of the nursing care (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that female nurses' satisfaction at work is lower than that of male nurses (15) . In addition, women are more affected by the characteristics of a bad work (16) environment and feel the pressure to balance work and family life, caring for children and house work (17) , which can result in increased salivary cortisol levels when compared to men (18) .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, it is common for nurses to work double shifts and receive low pay because of work shift scheduling (17) . When salivary cortisol levels are analyzed, the nurses who worked double shifts showed higher values on both work day and day off compared with nurses who had no other employment.…”
Section: Discussionmentioning
confidence: 99%